Tourism Management Education and Cultural Identity on Learning - Delgado, Rodolfo (Archives of Business Research, 2025)
This paper discusses the importance of cultural identity on learning. Interactive activities such as discussions, debates, short presentations, and critical thinking are conducted during classes to increase student talk time and contribute to information exchange and the acquisition of language and knowledge in the field of tourism management. This study seeks to understand, through qualitative research, all aspects of this situation. Therefore, short surveys were conducted, several groups were created, and students’ behavior, interactions, and performance were observed in the classroom. The results of the survey are interesting because while several students were expecting a 90-minute lecture where they were going to sit and just listen, the normal learning expectation of those with a normal Japanese cultural identity, other students enjoyed the discussion within the groups and acknowledged that interactive learning added value to the content and language acquisition process because they could analyze the information studied during the lessons.